PENSION COVERAGE AND CHILDREN'S EDUCATION INVESTMENTS IN INDONESIA - oktavina, monica; Gede Karma Wisana, I Dewa (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Pension guarantees have long been considered to provide benefits for retired households. Pension guarantee premium payments start while still working until before retirement. However, on the other hand, households must also prepare to invest in children's education. The existence of pension guarantees is thought to influence the allocation of household expenditure, especially children's education expenditure. This research wants to answer whether pension coverage can affect children's education expenditure through altruistic or non-altruistic parental motives. The relationship between pension security variables and children's educational investments was studied using collected cross-section data. The research results show a positive and significant relationship between pension fund coverage and children's education expenditure. It is hoped that this research can contribute to the government regarding the expansion of pension coverage to improve the welfare of households, especially older people and children, in the future.